Cost Comparison of Linezolid Versus Vancomycin for Treatment of Complicated Skin and Skin-Structure Infection Caused by Methicillin-Resistant Staphylococcus aureus in Quebec - Martine Pettigrew; Daniel JG Thirion; Michael Libman; Giovanni Zanotti (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In Canada, complicated skin and skin-structure infection (cSSSI) caused by methicillin-resistant Staphylococcus aureus (MRSA) is usually treated with antibiotics in hospital, with a follow-up course at home for stable patients. The cost implications of using intravenous and oral linezolid instead of intravenous vancomycin in Canadian clinical practice have not been examined.